DETERMINAN NIAT MELAKSANAKAN WHISTLEBLOWING INTERNAL PADA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA SURABAYA GUBENG - Yunita Haripuspita Amir; Hero Priono (BAJ: Behavioral Accounting Journal, 2021)
Whistleblowing system is designed to report violations or fraud that occur within an organization, however, it is often found that there are various obstacles that can prevent someone to become a whistleblower. A similar phenomenon occurs at the Surabaya Gubeng Pratama Tax Service Office, there are tax employees who are reluctant to carry out internal whistleblowing even though it is not significant. The population in this study is the tax employees who work at KPP Pratama Surabaya Gubeng totaling 109 people. The sampling technique used is simple random sampling, where the minimum sample size is based on Slovin, which is a minimum of 52 samples. This study was analyzed using the Partial Least Square (PLS) approach with the SmartPLS version 2.0.m3. The findings of this study are 1) awareness of employees work independently and carry out main tasks efficiently will encourage tax employees to report these violations to the right person, 2) awareness of employees an active role in increasing work productivity will let management top to find out violations, 3) The higher of employees complies with the rules and professional standards, higher report to supervisor regarding the violation, 4) seriousness of the violation will encourage employees to report the violation to the right person, 5) High or low the status of the violator will not affect the intention to carry out internal whistleblowing will encourage the tax employee to use the reporting channel, and 6) threat of the employees may receive will encourage the employees to use reporting channels.